2022
DOI: 10.1038/s42003-022-03573-9
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity mediates ecosystem sensitivity to climate variability

Abstract: A rich body of evidence from local-scale experiments and observational studies has revealed stabilizing effects of biodiversity on ecosystem functioning. However, whether these effects emerge across entire regions and continents remains largely overlooked. Here we combine data on the distribution of more than 57,500 plant species and remote-sensing observations throughout the entire Western Hemisphere to investigate the role of multiple facets of plant diversity (species richness, phylogenetic diversity, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 106 publications
0
10
0
Order By: Relevance
“…Spatial distribution of ecologically sensitive regions identified in this study is remarkably consistent with previous studies using different sensitivity metrics 4,44 , supporting the robustness of the pattern revealed in our study. Variability of ecosystem sensitivity has previously been suggested to be affected by many ecosystem attributes, such as species niche partitioning 50 , biodiversity 51,52 , ecosystem successional stage 53 , and landscape topography 54 . Our study suggests that at the global scale, properties of bedrock and its weathering products also have a significant effect on ecosystem sensitivity to climatic variability.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial distribution of ecologically sensitive regions identified in this study is remarkably consistent with previous studies using different sensitivity metrics 4,44 , supporting the robustness of the pattern revealed in our study. Variability of ecosystem sensitivity has previously been suggested to be affected by many ecosystem attributes, such as species niche partitioning 50 , biodiversity 51,52 , ecosystem successional stage 53 , and landscape topography 54 . Our study suggests that at the global scale, properties of bedrock and its weathering products also have a significant effect on ecosystem sensitivity to climatic variability.…”
Section: Discussionmentioning
confidence: 99%
“…Biodiversity plays an important role in the vegetation greenness IAV of terrestrial ecosystems. Oliveira et al (2022) found biodiversity mediates ecosystem sensitivity to climate variability-regions with greater plant diversity exhibit lower sensitivity to temperature variability at the interannual and seasonal scales and lower sensitivity to precipitation variability at the interannual scales. The increasing interannual variability of vegetation greenness might be related to decreasing biodiversity, particularly in China's Grain-for-Green Program (GFGP) regions, where GFGP forests are mostly monocultures or compositionally simple mixed forests (Hua et al 2016).…”
Section: The Environmental Driving Factormentioning
confidence: 94%
“…Trees over their long lifespan experience a multitude of severe conditions, but climate change is shifting essential phenological events and intensifying many of the environmental deviations. These deviations can exceed the reaction norms of trees [3][4][5][6][7][8]. For temperate trees, shifts in the spring arrival, and changing precipitation regimes can affect the phenological scheduling of vital biological events such as vessel activation [9], the acquisition of soil nutrients [10], flowering [3,[11][12][13], leaf flushing [14][15][16][17][18], xylogenesis [19], seeding and fruiting [20][21][22], and senescence-induced nutrient re-uptake from leaves [16,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%